Dynamics and Elastic Properties of Glassy Metastable States - Keiko M. Aoki (Solids, 2021)
By a molecular dynamics (MD) simulation method which ensures the system will be under hydrostatic pressure, dynamic and elastic properties of glassy metatstable states are investigated. In the MD method, the simulation cell fluctuates not only in volume but also in shape under constant hydrostatic pressure and temperature. As observed in experiments for many glass forming materials, metastable states in our simulation show a sharp increase in mean-square-displacement at certain temperatures <semantics>TD</semantics>. Dynamic heterogeneity is also observed at <semantics>TD</semantics>. Elastic properties are calculated from stress and strain relations obtained from the spontaneous fluctuation of internal stress tensor and simulation cell parameters. Each investigated state shows distinctive dynamics while maintaining solid-like elastic properties. The elastic properties stay intact even above <semantics>TD</semantics>. It has been shown that the rigidity and mobility of glassy metastable states are compatible under dynamic heterogeneity.